The relationship between performance motivational climate and coaches’ leadership behavior - Jakobek, Vedran; Ljubotina, Damir; Barić, Renata (23rd Psychology Days in Zadar: Book of Selected Proceedings, 2024)
In the context of competitive sports, the performance motivational climate is significantly shaped by a coach who gives different amounts of attention to athletes based on their talent level, punishes athletes for mistakes, and encourages rivalry between them. The aim of this paper is to broaden empirical knowledge about the relationship between performance motivational climate and different types of coaches’ leadership behaviors. A convenience sample in the present study consisted of 152 football players aged 15-18 years, who played in registered football clubs in the Republic of Croatia. The results showed that 28.3% of the variance in perceived performance motivational climate can be explained by coaching behaviors, with coaches’ Insensitivity to Athletes’ Well-being, Negative Feedback, and Results Orientation being statistically significant positive predictors.